K2O doped dolomite as heterogeneous catalyst for fatty acid methyl ester production from palm oil - Yahaya, Muhammad; Ramli, Irmawati; Muhamad, Ernee Noryana; Ishak, Nor Shafizah; Nda Umar, Usman Idris; Yap, Taufiq Yun Hin (Multidisciplinary Digital Publishing Institute, 2020)
Biodiesel obtained from palm oil over an environmentally friendly catalyst is highlydesirable. For that matter, dolomite, a natural material was used as a catalyst in this work, and this included potassium oxide (K2O)-doped dolomite, 5 wt% K/D, 10 wt% K/D, 15 wt% K/D, and 20 wt% K/D. X-ray diffraction analysis of dolomite revealed the CaO and MgO phases with high crystallinity, in which intensity reduced after doped with varying concentrations of K2O. When the catalysts were evaluated, the K2O-doped dolomite exhibited a better catalytic activity for palm oil transesterification. In the presence of K2O, the methyl ester reached 98.7%, with the highest being displayed by 15 wt% K/D as compared to 87% over dolomite at reaction temperature of 60 °C, 12:1 methanol to palm oil ratio, 1 wt% catalyst amount and 1 h reaction time. SEM revealed that as more K2O was doped on dolomite, the particles became more agglomerated, with a reduced BET surface area of 1.3 m2/g in 20 wt% K/D as opposed to homogeneously small-sized MgO and CaO particles in dolomite with a high BET surface area of 19.0 m2/g. However, the high activity of the doped catalyst was dictated by the high amount of basic site, as evidenced in TPD-CO2 which showed an increase in the capacity of the basic site with an increased amount of K2O. The catalyst was also reusable up to six times with a negligible decrease in activity due to K+ leaching.